(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Given the widespread belief in the literature that entrepreneurship can be taught, it is indisputable that the education system plays a crucial role in equipping prospective entrepreneurs with the knowledge and abilities they need. An entrepreneurial society and corporate culture can be fostered through education, which is becoming increasingly crucial as the demand for entrepreneurial knowledge, skills, and activities in all aspects of life rises. The present study further explores the relationship between entrepreneurial education and intention among undergraduates in Rivers State, Nigeria. One hundred and eleven undergraduates were randomly drawn from different institutions of higher learning in River State, Nigeria. Data for the study was gathered using structured questionnaires. The result showed a significant regression equation F (1,109), = 331.83, P<.05), indicating that EE significantly predicted EI among undergraduates with an R2 of 179, demonstrating that EE contributed 17.9% of the variation in the student's EI. Thus, the study's outcome confirms the hypothesis that EE would significantly predict EI among undergraduates in Rivers State. The practical implications and recommendations are discussed.